2020
DOI: 10.1186/s40035-020-00192-4
|View full text |Cite
|
Sign up to set email alerts
|

CSF total and oligomeric α-Synuclein along with TNF-α as risk biomarkers for Parkinson’s disease: a study in LRRK2 mutation carriers

Abstract: Background: Asymptomatic carriers of leucine-rich repeat kinase 2 (LRRK2) gene mutations constitute an ideal population for discovering prodromal biomarkers of Parkinson's disease (PD). In this study, we aim to identify CSF candidate risk biomarkers of PD in individuals with LRRK2 mutation carriers. Methods: We measured the levels of CSF total-(t-), oligomeric (o-) and phosphorylated S129 (pS129-) α-syn, totaltau (tTau), phosphorylated threonine 181 tau (pTau), amyloid-beta 40 (Aβ-40), amyloid-beta-42 (Aβ-42) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 33 publications
1
48
0
1
Order By: Relevance
“…Phosphorylated and oligomeric α-syn species may vary, depending on disease stage, in PD (i.e., preclinical vs. clinical vs. PD with dementia), raising the question of whether these α-syn species are in fact state or stage markers [18]. This correlation with disease stage was also evident in asymptomatic LRRK2 mutation carriers, as well as patients with idiopathic REM sleep behavior disorder (iRBD) [42][43][44]. In the present study, CSF α-syn species did not correlate with any clinical feature (i.e., disease duration, UPDRS).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated and oligomeric α-syn species may vary, depending on disease stage, in PD (i.e., preclinical vs. clinical vs. PD with dementia), raising the question of whether these α-syn species are in fact state or stage markers [18]. This correlation with disease stage was also evident in asymptomatic LRRK2 mutation carriers, as well as patients with idiopathic REM sleep behavior disorder (iRBD) [42][43][44]. In the present study, CSF α-syn species did not correlate with any clinical feature (i.e., disease duration, UPDRS).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygote PD GBA carriers were found to have elevated plasma levels of ferritin, CCL18 and MIP1␣ but heterozygotes PD and NMC did not differ from controls in their inflammatory profile [55]. While a small study with cations [25], CSF TNF-␣ was reported to be higher in 460 LRRK2-NMC than in controls [58]. However, these 461 findings were not replicated in other studies [57] or herein, possibly due to the lower age and number of controls in our study, use of concomitant inflammatory conditions as a covariate, and use of more stringent corrections for multiplicity in our study.…”
mentioning
confidence: 90%
“…E: Proteins involved in PD pathology; a commonly studied biomarker is α-synuclein. This protein has a tendency to be lower in PD; however, not all published studies have consistent results [196][197][198] . Studies with CSF total tau, phosphorylated tau, and amyloid-β protein and its variants also had inconclusive results 191,194,[199][200][201] .…”
Section: Cerebrospinal Fluidmentioning
confidence: 89%